Hot Standby: An Air Transportation Protocol to Reduce Organ Wastage. (August 2017) - Tomimatsu, Allison; Panzella, Tamiko Y.; Pritchard, Scott; Nguyen, John T.
Abstract : Purpose: Organ availability remains insufficient to meet the needs of nearly 120, 000 people waiting for transplant in the United States. Discarding scarcely available transplantable organs further widens this gap. With allocation strategies aimed towards broader sharing and maximizing outcomes, Organ Procurement Organizations (OPO) are exposed to a wider range of transplant centers (TXC) with distinctive acceptance thresholds; increasing risk for intraoperative declines. Preservation and logistical barriers necessitate innovative practices for successful reallocation. Methods: Intraoperative declines were reviewed to identify related risk factors. A Hot Standby (HS) air transportation protocol was utilized to reduce cold ischemic time (CIT) and increase potential to reallocate organs. Relationships were developed with TXCs willing to accept high risk grafts and invest resources allowing them to accept organs on short notice. Photographs of biopsy slides and organs along with physician-to-physician communication were additional tools for reallocation. HS was divided into three phases to manage OPO expenditures and ensure clear communication of transportation needs. Results: From July 2015 to January 2017, Phase B of the HS protocol was initated 26 times. More than half of these cases were escalated to Phase C, resulting in 14 rescued organs that were transplanted. The cancellation costs associated with Phase B, absorbed by the OPO, was nearly 15, 000. With an average organ acquisition cost (OAC) of 50, 000, the HS cancellations fees during this 18-month period were recouped by a single, rescued organ. Conclusion: OPOs can utilize HS to reduce the challenges of reallocating organs declined intraoperatively. The recovered OACs provided a return of over 4500% on cancellation fees, which demonstrates a highly effective method for increasing utilization. This margin suggests the need to more liberally apply this protocol. HS can be enhanced by establishing triggers for initiating this protocol based on discard data. Policies should aim to eliminate inefficiencies around expedited allocation. Considering waitlist mortality and the scarcity of organs, every opportunity to maximize the gift must be seized. HS presents low financial risk and high reward. Most importantly it reduces organ wastage and advances the mission of saving lives. We hereby express our thanks to all Donor Network West staff, healthcare partners and organ and tissue donors and their families, for giving the gift of life and knowledge through their generous donation . Figure. No caption available. Figure. No caption available. Figure. No caption available.